THE PROBATORY ACTIVITY AND THE IMPARTIAL THIRD PARTY IN THE CONTRADICTORY ACCOUNT MODEL OF THE CRIMINAL PROCEDURAL CODE (DEC. LEG. N.° 957) - Castro Medina, Rodolfo (2017)
This article is concerned with pointing out and believing that the Criminal Procedure Code of 2004, considering the judgment stage as a main phase of the criminal proceedings under the principles of orality, publicity, immediacy, contradiction and procedural equality, among others, would demonstrate a clearly established delimitation of functions, both for the procedural parties, as well as for the impartial third party, forming a triadic scenario in the judgment. Therefore, beyond the observation, control and direction of the oral judgment, it would be counterproductive to accept some judicial intervention in the probative activity as also prescribed in the said adjective code. The objectives of the study are to identify which procedural and structural principles that govern the oral trial are violated with the powers of intervention of the judge of judgment within the framework of the Code of Criminal Procedure of 2004; analyze the concept and attributions of being the impa